Growth of service sector in BRIIC economies - Maisya Farhati; Raquel Ortega-ArgilÃ©s (Universitas Islam Indonesia, 2018)
In recent years, there has been growing attention to service sector in theworld economies. This study analyses service sector in Brazil, Russia, India,Indonesia and China (BRIIC), which are five of the largest economies intodayâ€™s developing world. We examine how the services links with overalleconomic activities and what drives its growth in the period 2000-2010.This research finds that in BRIIC economies, final demand in other sectorshas not enhanced services output. Furthermore, using structuraldecomposition analysis, this study investigates various aspects whichcontribute to the growth of services output, which are final domesticdemand, export, and changes in technology. The result suggests that inBRIIC economies, final domestic demand has been the main driver of thegrowth of services that exceeded more than 70% of overall effect in alleconomies. Domestic final demand for services contributed higher than thenon-services one.